The Effect of Products and Promotions on Investment Interest of Graduate Students of UIN Raden Intan Lampung in Sharia Mutual Funds - Siti Maisaroh; Dian Ekawati; Heni Noviarita (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
The choice of placing funds in Mutual Fund products by investors is increased by 3.14% from 2020 to 2021 with a total NAV of IDR 77.51 trillion. However, there are several obstacles that affect the development of investment in Sharia Mutual Fund products. The study aims to examine the effect of products and promotions on the investment interest of students in sharia mutual funds. The method of research used is quantitative and data analysis used multiple regression tests. Collecting data using a questionnaire with respondents coming from Postgraduate Students of UIN Raden Intan Lampung. The results of this study indicate that the results of the determination test of the magnitude of the product's influence on investment interest are 76.4%. The remaining 23.6% is influenced by other variables and the effect of promotion on investment interest is 22.1%, the remaining 77.9% is influenced by other variables not discussed in this study.